2020
DOI: 10.1126/science.aay9333
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary dynamics and fitness landscape of clonal hematopoiesis

Abstract: Somatic mutations acquired in healthy tissues as we age are major determinants of cancer risk. Whether variants confer a fitness advantage or rise to detectable frequencies by chance remains largely unknown. Blood sequencing data from ~50,000 individuals reveal how mutation, genetic drift, and fitness shape the genetic diversity of healthy blood (clonal hematopoiesis). We show that positive selection, not drift, is the major force shaping clonal hematopoiesis, provide bounds on the number of hematopoietic stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
361
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(437 citation statements)
references
References 70 publications
35
361
4
2
Order By: Relevance
“…Using the structure of the HSC lineage tree, we inferred the fitness advantage of JAK2-mutated HSCs in 2 MPN patients during the pre-diagnosis period to be approximately 40-65%. Our inferred fitness advantage is larger than that found in a population-level study of CHIP, which analyzed peripheral blood variant allele fractions in large cohorts of individuals 40 . This discrepancy suggests that the development of full-blown MPN may require a faster-growing JAK2-mutant clone than that observed in clonal hematopoiesis.…”
Section: Discussioncontrasting
confidence: 68%
“…Using the structure of the HSC lineage tree, we inferred the fitness advantage of JAK2-mutated HSCs in 2 MPN patients during the pre-diagnosis period to be approximately 40-65%. Our inferred fitness advantage is larger than that found in a population-level study of CHIP, which analyzed peripheral blood variant allele fractions in large cohorts of individuals 40 . This discrepancy suggests that the development of full-blown MPN may require a faster-growing JAK2-mutant clone than that observed in clonal hematopoiesis.…”
Section: Discussioncontrasting
confidence: 68%
“…Some of these events were identical and occurring in both compartments. This is in line with the findings from other healthy tissues, which all confirm the presence of mutations in cancer-associated genes in the normal epithelium and blood 1,[3][4][5][6][7]24 . However, in the breast, there is preferential accumulation of mutations in ESR1 and RUNX1, mutated in approximately 60% of samples in the parous and nulliparous group, respectively (Fig.…”
Section: Mutational Burden Within Breast-cancer Associated Genessupporting
confidence: 90%
“…As we demonstrated in Williams et al 21 , mutation frequency and driver dN/dS are expected to be positively associated showing the highest values at the largest clone sizes (Fig 2B). Accordingly, and as observed recently in clonal hematopoiesis 22 , the allele frequency spectrum (Cancer Cell fraction or CCF) of synonymous and non-synonymous mutations (Fig. 2C) showed that the observed high driver dN/dS is a consequence of proportionally fewer synonymous mutations at higher CCF thresholds compared to nonsynonymous mutations.…”
Section: Evolutionary Dynamics Of Dn/ds During Immunoediting Reveals supporting
confidence: 88%
“…The application of evolutionary theory allows us to infer cell growth dynamics, the number of driver alterations 17,18 and their selective fitness coefficients [19][20][21][22] , as well as the impact of deleterious mutations during cancer progression 23,24 . An evolutionary metric recently used to detect selection in cancer studies is the ratio of nonsynonymous to synonymous mutations, dN/dS 7,8,[25][26][27] .…”
Section: Introductionmentioning
confidence: 99%